2018
DOI: 10.1002/cnr2.1110
|View full text |Cite
|
Sign up to set email alerts
|

WT‐CLS1 is a rhabdoid tumor cell line and can be inhibited by miR‐16

Abstract: Background: Wilms tumor and rhabdoid tumor can have similar clinical presentations, but they have distinct histological and biological features. For instance, Wilms tumors commonly bear mutations in kidney differentiation or microRNA processing genes, whereas rhabdoid tumor is characterized by loss of SMARCB1. Aims:We initially set out to characterize and identify tumor suppressor microRNAs in WT-CLS1, which had been described as a Wilms tumor cell line. Methods and Results:We characterized the cell line WT-CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…The development and testing of preclinical therapies focusing on these key groups of WT patients have been limited by the paucity of available relevant in vitro and in vivo WT models 17 . The one commercially available, purported WT cell line (WT-CLS1) was recently reclassified as a malignant rhabdoid tumor due to presence of hemizygous SMARCB1 mutation 18 . The G401 cell line was also previously reclassified as a rhabdoid tumor line 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…The development and testing of preclinical therapies focusing on these key groups of WT patients have been limited by the paucity of available relevant in vitro and in vivo WT models 17 . The one commercially available, purported WT cell line (WT-CLS1) was recently reclassified as a malignant rhabdoid tumor due to presence of hemizygous SMARCB1 mutation 18 . The G401 cell line was also previously reclassified as a rhabdoid tumor line 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Especially since over the years some of them have been re-evaluated and been designated as other tumour entities based on for instance their genetic profiles. [26][27][28] Tumour genetics could also explain why the two cell lines respond differently. SIX2 is recurrently mutated in Wilms tumour, but mutations in the gene do not seem to affect SIX2 protein expression according to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…(F) A receiver-operating characteristic curve demonstrates the prognostic power of diagnostic urine prohibitin to predict abdominal relapse in favorable-histology Wilms' tumor at different sensitivity and specificity with an AUC of 0.96 (95% CI, 0.91-1.0). tumor of the kidney due to the presence of disease-defining SMARCB1 mutation (20). Using quantitative fluorescent Western blot immunoassays, we found that PHB is more highly expressed in renal tumor cell lines, as compared with BJ fibroblasts ( Figure 4A).…”
Section: Comparative Urine Proteomics Of Wilms' Tumor Kidney Rhabdoimentioning
confidence: 97%